Қарақалпақстан аймағында өсиўши жуўсан – artemisial өсимлиги - Атамуратов, Р; Оразбаева, А (SCIENCE and SOCIETY, 2019)
The article deals with information on the value and practical meaning of the plant Wormwood which is actively used by people in medicine, cattle breeding and in everyday life. The authours of the article proved evidence of wide use of the species of the plants of Wormwood growing on the territory of Karakalpakstan.
Keywords: complex flower seedbuds; Wormwood – Artemisia L; healing power; people’s medicine; wideuse in pharmacy; Artemi- sia arenaria DC; Artemisia diffusia; Artemisia halophila Krash